Preliminary study of gasification of Argan’s nutshells in a fluidized bed gasifier - Afailal, Zainab; Gil-Lalaguna, Noemí; Fonts Amador, Isabel (Jornada de Jóvenes Investigadores del I3A, 2018)
The main objective of this study is to assess the performance of the gasification of Argan’s nutshells with pure oxygen as gasification agent. The results of the experiments gave an important percentage of hydrogen produced, around 20%, and point to this agricultural waste as an interesting material to be gasified.